ANALYSIS OF THE INFLUENCE OF PRODUCT AVAILABILITY, PRICE, AND DISCOUNTS ON CUSTOMER LOYALTY AT VAPE STORES IN SUKOHARJO - Johan Surya Prayoga; Erni Widiastuti (LPPM STIE EKA PRASETYA, 2025)
This study aims to analyze the effect of product availability, price, and discount on customer loyalty at vape stores in the Sukoharjo area periode of year 2025. A quantitative approach was used with a survey method. The sampling technique applied was purposive sampling, involving 100 respondents who are customers of vape stores in the region. Data were collected through questionnaires and analyzed using SPSS version 30. The data analysis techniques included validity testing, reliability testing, classical assumption tests (normality, multicollinearity, and heteroscedasticity), F-test, t-test, multiple linear regression, and determination coefficient ( ). The results showed that product availability, price, and discount have a significant influence on customer loyalty, both simultaneously and partially. These findings suggest that vape store owners should ensure consistent product availability, implement competitive pricing strategies, and offer attractive discounts to enhance customer loyalty.